The Diagnostic and Prognostic Value of suPAR in Patients with Sepsis: A Systematic Review and Meta-Analysis - Huang, Qiangru (Shock, 2020)
BACKGROUND: Soluble urokinase-type plasminogen activator receptor (suPAR) has the potential to diagnose infectious diseases. Due to the lack of reliable biomarkers and the importance of timely diagnosis for sepsis treatment, we conducted this systematic review and meta-analysis to evaluate the value of suPAR diagnosis and prognosis for sepsis. METHODS: PubMed, Embase, Web of Science, and Cochrane Library databases were searched for studies, which reported the value of suPAR diagnosis and/or prognosis in patients with sepsis. RESULTS: A total of 30 studies involving 6,906 patients were included. Sensitivity and specificity of suPAR for diagnosing sepsis were 0.76 [95% confidence interval (CI), 0.63–0.86] and 0.78 (95% CI, 0.72–0.83), respectively. The area under the summary receiver-operating characteristic curve (AUC) was 0.83 (95% CI, 0.80–0.86). Pooled sensitivity and specificity for predicting mortality were 0.74 (95% CI, 0.67–0.80) and 0.70 (95% CI, 0.63–0.76), respectively, with AUC of 0.78 (95% CI, 0.74–0.82). In addition, AUC for differentiating sepsis from systemic inflammatory response syndrome (SIRS) was 0.81 (95% CI, 0.77–0.84), and the sensitivity and specificity were 0.67 (95% CI, 0.58–0.76) and 0.82 (95% CI, 0.73–0.88), respectively. CONCLUSION: suPAR is a feasible biomarker for timely diagnosis and prognosis of sepsis. Compared with effective value of procalcitonin (PCT) identified by previous meta-analysis, suPAR has similar clinical guiding value, whereas suPAR exhibits higher specificity, which can facilitate the deficiencies of PCT. suPAR also shows a diagnostic value in differentiating sepsis from SIRS. Considering the lack of biomarkers for sepsis and the similar clinical value of suPAR and PCT, suPAR should be considered as a biomarker in clinical practice for sepsis.